Vertical distribution of rare earth elements in a wetland soil core from the Sanjiang Plain in China - 程红光 郝芳华 欧阳威 刘少卿 林春野 杨文静 (Journal of rare earths, 2012)
The objective of this study was to investigate the vertical distribution of rare earth elements （REEs） in a natural wetland soil core to understand the influence of natural and anthropogenic activities on geochemical behavior of REEs. A natural wetland soil core of 95 cm was collected from the Sanjiang Plain in China and sliced into 5 cm slices for analyses of REEs, Fe, Al, Mn, Sc, Y, and soil organic matter （SOM）. Results indicated that SOM was accumulated in the upper part of the soil core （0 to 20 cm depth）, while Fe and Mn was reductively leached from the upper part of the soil core and accumulated in the low part. The content of total REEs ranged from 137.9 to 225.9 mg/kg in the soil core. Content profiles obtained for all REEs were almost identical except for Ce. The highest contents of REEs generally occurred at about 20 cm depth, but enrichment factor （EF） of REEs except Ce was usually the highest in the surface horizon. Average EF ranged from 1.1 for La to 2.1 for Gd. The pronounced shift in EF occurred at about 40 cm depth and it gradually increased from 40 cm depth to surface （except for Ce）, probably suggesting anthropogenic atmospheric deposition of REEs. In comparison with chondrite, Eu was depleted in all horizons, while Ce was negatively anomalous in the top horizons and positively anomalous in the bottom horizons. This positive anomaly of Ce in the bottom horizons was due to its preferential adsorption on Fe and Mn oxides, relative to other REEs. Although both natural and anthropogenic activi-ties influence the geochemical behaviors of REEs in soils, enrichment or mobility of REEs is low in the natural wetland soil core of the San-jiang Plain.